Numerical Analysis of a Hydrodynamic Herringbone Grooved Journal Bearing - D. Souchet; A. Senouci; H. Zaidi; M. Amirat (Journal of Engineering)
In hydrodynamic lubrication, at very high rotational speed, the phenomenon of axial fluid leakage is often present. This can involve an increase of shear stress in the contact and consequently a considerable increase of the temperature. For that and in order to solve this problem, we took interest in the herringbone grooved journal bearings. The researches made before on these types of groove bearing have shown that they present a good dynamical behavior with a low eccentricity and a low axial flow. In this paper, a numerical study of a herringbone journal bearing operating behavior, under laminar and isothermal regime, is presented. The theoretical model, based on the classical Reynolds equation, is used. In order to include the film rupture and reformation, the Reynolds equation is modified using a mass conservative algorithm. To understand the behavior of these herringbone grooved journal bearings well, numerical modeling, using finite element method, has been developed. Various geometrical shapes of the herringbone grooved journal bearings have been analyzed, allowing us to limit the fluid leakage problem, by working particularly on the contact form.